Respuesta :
Answer:
B. (-1,-5)
Step-by-step explanation:
Line 1 (Table A):
[tex]y-(-2)=\dfrac{-2-(-8)}{0-(-2)}\cdot (x-0)\\ \\ \\y+2=\dfrac{6}{2}\cdot x\\ \\y=3x-2[/tex]
Line 2 (Table B):
[tex]y-(-5)=\dfrac{-9-(-5)}{-3-(-1)}\cdot (x-(-1))\\ \\ \\y+5=\dfrac{-4}{-2}\cdot (x+1)\\ \\y+5=2x+2\\ \\y=2x-3[/tex]
Equate these two equations:
[tex]3x-2=2x-3\\ \\3x-2x=-3+2\\ \\x=-1[/tex]
Substitute it into the first equation:
[tex]y=3\cdot (-1)-2=-3-2=-5[/tex]
The solution to the system of equations is (-1,-5)